2018
DOI: 10.1161/atvbaha.118.311233
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gut Microbiota and Diet on the Development of Atherosclerosis in Apoe −/− Mice

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 44 publications
10
95
1
2
Order By: Relevance
“…Plasma TMAO concentration is positively correlated to the mortality risk in patients with stable coronary artery disease, carotid intima‐media thickness in obese individuals or patients with thrombosis risk (Kiouptsi & Reinhardt, ; Randrianarisoa et al, ; Senthong et al, ; Wang et al, ; Zhu et al, ). TMAO has been shown to exacerbate atherosclerosis in apolipoprotein E (ApoE) knockout mouse model (Wang et al, ) while Jonsson et al found no correlation between plasma TMAO concentrations and atherosclerotic lesion size (Lindskog Jonsson et al, ). This discrepancy could be due to the difference in experimental design.…”
Section: Gut Microbiota and Cardiovascular Healthmentioning
confidence: 99%
“…Plasma TMAO concentration is positively correlated to the mortality risk in patients with stable coronary artery disease, carotid intima‐media thickness in obese individuals or patients with thrombosis risk (Kiouptsi & Reinhardt, ; Randrianarisoa et al, ; Senthong et al, ; Wang et al, ; Zhu et al, ). TMAO has been shown to exacerbate atherosclerosis in apolipoprotein E (ApoE) knockout mouse model (Wang et al, ) while Jonsson et al found no correlation between plasma TMAO concentrations and atherosclerotic lesion size (Lindskog Jonsson et al, ). This discrepancy could be due to the difference in experimental design.…”
Section: Gut Microbiota and Cardiovascular Healthmentioning
confidence: 99%
“…In CONV-R Ldlr −/− mice, no microbiota-dependent effects were observed on late atherosclerotic lesion size on a γ-irradiated cholesterol-rich diet at sixteen-weeks of Western diet feeding with respect to GF counterparts [48]. In accordance to this recent work, Lindskog Jonsson et al did not find a correlation between plasma TMAO concentration and atherosclerotic lesion size in the aortic root and the relative aortic root lesion size was not significantly different in GF Apoe −/− C57BL/6J mice, compared to CONV-R Apoe −/− C57BL/6J mice treated with a Western diet [9,14]. A previous study on GF Apoe −/− C57BL/6 mice kept on a chow diet reported reduced relative and absolute aortic root plaque areas and reduced macrophage plaque content at twenty-weeks of age [15] (Figure 1).…”
Section: Patterns and Metabolites From The Gut Microbiota As Driversmentioning
confidence: 53%
“…Interestingly, plasma L-carnitine levels were identified as a predictor of cardiovascular risk in coronary artery disease and peripheral artery disease patients and both dietary choline and TMAO supplementation enhanced atherosclerotic lesion development in atherosclerosis-prone Apoe −/− C57BL/6J mice [12,13]. Of note, this was not found in studies with GF Apoe −/− mice [14]. While choline supplemented diet augmented atherosclerosis and plaque macrophage content in this mouse atherosclerosis study, broad-spectrum antibiotic treatment (0.5 g/L vancomycin, 1 g/L neomycin sulfate, 1 g/L metronidazole, 1 g/L ampicillin) via the drinking water demonstrated that depletion of the microbiota decreased the choline-dependent enhancement of atherosclerotic lesions in male and female Apoe −/− C57BL/6J mice, when kept on a choline-enriched diet at the age of four-weeks until the age of twenty-weeks [16].…”
Section: Patterns and Metabolites From The Gut Microbiota As Driversmentioning
confidence: 98%
See 1 more Smart Citation
“…Acute administration of these products enhanced Spp1 expression in circulating Ly6C hi monocytes, and chronic LPS and TMAO administration accelerated atherosclerosis development. Although associations between circulating TMAO and the risk of cardiovascular events has been demonstrated, reports are inconsistent (Qi et al, 2018) and the role of TMAO in atherosclerosis has not yet been fully elucidated (Lindskog Jonsson et al, 2018). Perhaps TMAO exerts its effects in the setting of inflammation, such as in the presence of LPS.…”
Section: Previewsmentioning
confidence: 99%